Clinical evolution and epilepsy outcome in three patients with CDKL5‐related developmental encephalopathy. Issue 3 (17th July 2019) - Bernardo, Pia; Ferretti, Alessandro; Terrone, Gaetano; Santoro, Claudia; Bravaccio, Carmela; Striano, Salvatore; Coppola, Antonietta; Striano, Pasquale
ABSTRACT: Aims . To further characterise CDKL5 ‐related disorder, previously classified as an early‐onset seizure variant of Rett syndrome, which is currently considered a specific and independent early‐infantile epileptic encephalopathy. Methods . We describe the epileptic phenotype and neurocognitive development in three girls with CDKL5 mutations showing severe neurodevelopmental impairment, with different epileptic phenotypes and severity. Results . The patients differed regarding age at epilepsy onset, seizure frequency, duration of "honeymoon periods", as well as EEG features. The "honeymoon period", defined as a seizure‐free period longer than two months, represented, in our case series, a good indicator of the epilepsy outcome, but not of the severity of developmental impairment. However, even during the "honeymoon period", the interictal EEG showed epileptiform abnormalities, slowing, or a disappearance of physiological pattern. The natural history of CDKL5 disorder was compared between the three girls, focusing on the relationship between electroclinical features and neurological development. Conclusion . Our findings suggest that CDKL5 mutations likely play a direct role in psychomotor development, whereas epilepsy is one of the clinical features associated with this complex disorder.